Semitic Loan Words in the Gospel of John: Elements of Antilanguage or Points of Contact? = Semitskie zaimstvovanija v Evangelii ot Ioanna: Ėlementy «antijazyka» ili točki soprikosnovenija? - Ustinovich, Yevgeny (Bogoslovskie razmyšlenija, 2014)
This article analyzes sociolinguistic as pects of three Semitic words used in theGospel of John. Since all these words had wellestablished Hellenistic equivalents in the time of John's writing, their use may be interpreted as a deliberate attempt to establish additional points of contact with nonbelieving Jewish readers. In that case, the use of the convergent forms [~abbi,], [Messi,aj], and [~Wsanna,] in the Fourth Gos pel does not support the hypothesis of "antilanguage" in John and makes one reconsider the results of the research based on that concept.